Heterogeneity in Rent-Seeking Contests with Multiple Stages: Theory and Experimental Evidence - Tanja Hörtnagl; Rudolf Kerschbamer; Rudi Stracke; Uwe Sunde (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper investigates how heterogeneity in contestants' investment costs affects the competition intensity in a dynamic elimination contest. Theory predicts that the absolute level of investment costs has no effect on the competition intensity in homogeneous interactions. Relative cost differences in heterogeneous interactions, however, reduce equilibrium expenditures. Evidence from lab experiments for treatments with homogeneous participants is qualitatively in line with the theoretical prediction. The effect of cost differences on expenditures is positive rather than negative, however, in all heterogeneous treatments.
Keywords: C72; D72; 330; multi-stage contest; heterogeneity; experiment; joy of winning